Did Focusing on Asia Pacific Emerging Markets Provide Much Benefit to Portfolio Diversification during the Late 2000s Recession? - Hermanto, Bambang; Indra, Fajar (The Indonesian Capital Market Review, 2013)
This research studies the international co-movement among Asia Pacific emerging markets stock price indices during the late 2000s recession by using the monthly observations start from 1st October 2001 until 1st April 2011. The co-integration analysis and parsimonious Vector Error Correction Model employed in this research reveal a long-term relationship and inter-dependencies among seven Asia Pacific emerging market stock price indices. This research finds that the unique co-integration exists on the equations. Specifically, two indices from China and Taiwan having meteor shower potential while the rest indices from Thailand, Malaysia, and Indonesia are known to have heat waves effects or country specific factors on the equation. Finally, all the results are linked to the international diversification strategies